CT and MRI presentation of nasopharyngeal tuberculosis (with a case report) - Jingjing Tang; Huijuan Chen; Feng Chen (Radiology Case Reports, 2024)
Nasopharyngeal tuberculosis is a rare extrapulmonary tuberculosis caused by Mycobacterium tuberculosis invading the nasopharynx. Early clinical symptoms are atypical, making the condition easy to overlook and misdiagnosed. We retrospectively reviewed the case of a 37-year-old man who visited the clinic in March 2023, presenting with enlarged cervical lymph nodes persisting for over a year. Computed tomography and magnetic resonance imaging showed the nasopharynx wall was thickened, and cervical multiple enlarged lymph nodes were visible, presenting bead-like appearance. The enhanced scan revealed the lesion uneven enhancement. He was diagnosed with nasopharyngeal carcinoma with lymph node metastasis based on the images. However, the histopathological examination finally confirmed that the nasopharyngeal and neck mass were tuberculous granulomas. Nasopharyngeal tuberculosis is easily misdiagnosed and mistreated, and it is especially difficult to differentiate from nasopharyngeal carcinoma. When diagnosing and treating neck masses, clinicians should consider the possibility of nasopharyngeal tuberculosis in patients with chronic nasopharyngeal symptoms. Nasopharyngoscope biopsy and histopathological examination have great value in the diagnosis of nasopharyngeal tuberculosis.